Cover Image. (16th December 2021) - Strasser, Bernhard; Arango, Nicolas S.; Stockmann, Jason P.; Gagoski, Borjan; Thapa, Bijaya; Li, Xianqi; Bogner, Wolfgang; Moser, Philipp; Small, Julia; Cahill, Daniel P.; Batchelor, Tracy T.; Dietrich, Jorg; et al.
Abstract : The cover image is based on the Research Article Improving D‐2‐hydroxyglutarate MR spectroscopic imaging in mutant isocitrate dehydrogenase glioma patients with multiplexed RF‐receive/B0‐shim array coils at 3 T by Bernhard Strasser et al., https://doi.org/10.1002/nbm.4621 .